Earthquake Risk Assessment of Sabah, Malaysia Based on Geospatial Approach - Sauti, Noor Suhaiza; Daud, Mohd Effendi; Kaamin, Masiri; Sahat, Suhaila (International Journal of Integrated Engineering, 2022)
Sabah is located in the northeast region of East Malaysia and recognized as the most active seismic areas in Malaysia. The scalability and frequency of earthquakes are growing due to the existence of both local and distant ground motions from active faults, with more than 100 earthquake events have been recorded since 1923. On the other hand, the skewed socio-economic development process associated with the rapid population growth and changes in the family structure, inequality issues, and the lack of adaptation measures would intensify the vulnerability of the earthquakes. Key elements linked to socio-economic vulnerability need to be address in order to reduce the risk of earthquake. Based on previous studies, we identified vulnerabilities from a multi-dimensional perspective consisting of exposure, resilience and capacity across districts. Subsequently, a holistic indicators system with 18 variables was constructed to assess the potential earthquake vulnerability in Sabah, Malaysia. The accumulated data will present an earthquake vulnerability classification using a Geographical Information System (GIS) approach. Finally, the earthquake risk was derived by integrating the earthquake vulnerability map with earthquake hazard map proposed by the Department of Mineral and Geoscience (JMG) Malaysia. The results of the analysis revealed that the highest levels of earthquake risk accounts for 15.5% were concentrated in the eastern part of the Sabah region; the high-risk areas accounts for 7.7%; the moderate-risk areas accounts for 11.3%; and the area of low to very low risk accounts for 65.4%. Accordingly, it is expected that the derived earthquake vulnerability and risk map will allow the policymakers and response teams to improve the earthquake disaster mitigation and management in Sabah.